2019
DOI: 10.4012/dmj.2018-306
|View full text |Cite
|
Sign up to set email alerts
|

R.T.R<sup>®</sup> promotes bone marrow mesenchymal stem cells osteogenic differentiation by upregulating BMPs/SMAD induced <i>cbfa1</i> expression

Abstract: Bone marrow mesenchymal stem cells (BMSCs) of rats were isolated and Bio-Oss ® and R.T.R ® materials were used in this study. Alkaline phosphatase (ALP) activity in each group was calculated. The ability of adhesion and proliferation of BMSCs on Bio-Oss ® and R.T.R ® increased with time, but they were significantly higher on R.T.R ® than that of Bio-Oss ® at all time points (p<0.05). Compared with Bio-Oss ® , R.T.R ® could promote the expression and activity of ALP in BMSCs, and the expression of bone formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that rhBMP-2 is inferior to allografts in regard to surgical supply costs [96] and complications rates [97]. Furthermore, CBSs (TCP, HA, SiO 2 ) are able to upregulate BMP-2 expression via plasma cell glycoprotein-1, which is restricted in expression to those cells that are in direct contact to CaP surfaces [98,99]. Here, ectonucleotide pyrophsphatase/ phosphodiesterase 1(ENPP1)/plasma cell glycoprotein 1 (PC-1) plays a key role in osteoinduction by CaP ceramics; PC-1 expression is restricted to those cells that are in direct contact to CaP surfaces, downregulating ENPP1-expression and upregulating BMP-2 expression [100].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that rhBMP-2 is inferior to allografts in regard to surgical supply costs [96] and complications rates [97]. Furthermore, CBSs (TCP, HA, SiO 2 ) are able to upregulate BMP-2 expression via plasma cell glycoprotein-1, which is restricted in expression to those cells that are in direct contact to CaP surfaces [98,99]. Here, ectonucleotide pyrophsphatase/ phosphodiesterase 1(ENPP1)/plasma cell glycoprotein 1 (PC-1) plays a key role in osteoinduction by CaP ceramics; PC-1 expression is restricted to those cells that are in direct contact to CaP surfaces, downregulating ENPP1-expression and upregulating BMP-2 expression [100].…”
Section: Discussionmentioning
confidence: 99%